2013
DOI: 10.5468/ogs.2013.56.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Type-specific prevalence of high-risk human papillomavirus by cervical cytology and age: Data from the health check-ups of 7,014 Korean women

Abstract: ObjectiveWe investigated the type-specific high-risk human papillomavirus (HPV) prevalence and distribution according to cervical cytology and age in healthy Korean women.MethodsA retrospective cross-sectional study was conducted with 7,014 consecutive subjects undergoing both liquid-based cervical cytology and HPV genotyping test by DNA chip for cervical cancer screening. The type-specific prevalence and distribution of individual high-risk HPV types were assessed according to cervical cytology and age groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 36 publications
6
43
4
Order By: Relevance
“…Among the definite high‐risk types, HPV‐52, 16 and 58 were top 3 common types in the present and previous [Onuki et al, ; Inoue et al, ] studies in Japan, Korea [Kim et al, ], and many Chinese areas [Wu et al, ; Ye et al, ; Chen et al, ], although HPV‐52 was not so common in Mongolia [Dondog et al, ]. In contrast, HPV33, 35 and 45 were rarest in the present and the previous Japanese study [Inoue et al, ], Costa Rica [Herrero et al, ], USA [Wheeler et al, ] and worldwide [Bruni et al, ] studies, while HPV35 was relatively common in Korea [Kim et al, ] and Mongolia [Dondog et al, ]. Surprisingly, HPV‐35 was more common than HPV‐52 in Mongolia.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Among the definite high‐risk types, HPV‐52, 16 and 58 were top 3 common types in the present and previous [Onuki et al, ; Inoue et al, ] studies in Japan, Korea [Kim et al, ], and many Chinese areas [Wu et al, ; Ye et al, ; Chen et al, ], although HPV‐52 was not so common in Mongolia [Dondog et al, ]. In contrast, HPV33, 35 and 45 were rarest in the present and the previous Japanese study [Inoue et al, ], Costa Rica [Herrero et al, ], USA [Wheeler et al, ] and worldwide [Bruni et al, ] studies, while HPV35 was relatively common in Korea [Kim et al, ] and Mongolia [Dondog et al, ]. Surprisingly, HPV‐35 was more common than HPV‐52 in Mongolia.…”
Section: Discussionsupporting
confidence: 54%
“…HPV‐52 was the most common type in the present study, another Japanese study [Inoue et al, ] and the above areas of China, while HPV‐16 was the most common type in the other Japanese study [Onuki et al, ] and other countries, including one area in China (Shenzhen city) [Wu et al, ], Mongolia [Dondog et al, ], Costa Rica [Herrero et al, ], the USA [Wheeler et al, ], and worldwide [Bruni et al, ] (Table ). In Korea, the most common type was HPV‐58 [Kim et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…From another perspective, women in the menopausal period have reduced immune functions, with decreased viral clearance rates and increased HPV infection rates. Therefore, there are two peaks in the age distribution of HPV infection: 15–24 year olds and women >54 years [28, 29]. In the present study, the HPV infection rates in the different age groups showed the highest HPV infection rate of 34.7% in the 15–24-year-old group, followed by an infection rate of 24.1% in the >54-year-old group.…”
Section: Discussionsupporting
confidence: 49%
“…In our study, HPV58 was the second most common types no matter in normal, ASCUS, LSIL cytology samples or in LSIL pathology specimens, we didn't detect HPV58 neither in HSIL cytology samples nor in HSIL, SCC pathology specimens considering small samples. However, the carcinogenicity of HPV58 cannot be ignored, some previous studies have demonstrated HPV 58 were more prevalent in cervical cancer cases in Asia [Bao et al, 2008b;Kim et al, 2013]. The prevalence of HPV18 (1.57%) was lower compared to HPV16 and 58 in this general population, although it was reported as the secondly common types in the metaanalysis of worldwide studies and caused 70% of cervical cancers with HPV16 [shomo et al, 2014].…”
Section: Discussionmentioning
confidence: 75%